LIMITS OF INTERACTION OF RUSSIAN AND CHINESE BUSINESS IN THE COUNTRIES OF EURASIAN ECONOMIC UNION - A. V. Kuznetsov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2017)
The article is dedicated to the possibility of joining the Russian and Chinese integration initiatives on the EEU space from the side of business-actors. The author stresses the necessity for a wider type of analysis, which would not be limited by such narrow research object as perspectives of the so-called Silk Road Economic Belt. The study is based on the statistic analysis of the partnerstates foreign trade and official information, as well as expert evaluation of the investments` scale and structure. Besides, the author collected data about the direct investment provided by Chinese and Russian TNC in order to support the EEU member-states (directly or via third states). The significant part of the article is dedicated to the issues of competition between the Chinese and Russian TNC in Kazakhstan and Kyrgyzstan and possibilities of the fruitful cooperation between those businesses in Central Asia. The author also sheds light on the growing impact of the Chinese business in Belarus and Armenia, where Russian firms are the most powerful foreign economic actors, what, nevertheless, does not re duce the significant impact of the Western European and other TNC. Those considerations are followed by the author`s examination of the limitation of the ChinaRussia business partnership in Russia itself; the author also presents an original comparative analysis of the Chinese direct investments in Russia and vice versa. Finally, the author attempts to verify the hypothesis about the positive perspectives of the Russia-China economic partnership outside of the post-soviet space. The author claims that the lack of such a cooperation between Russian and Chinese TNCs in Africa or Latin America illustrates the power of political limiting factors, rather than the absence of mutual interest of the parties.